대구·경북 지역 방사선학과 재학생의 법의학 인식 및 관심도 분석 - 박창희; Chang-hee Park (한국방사선학회 논문지, 2024)
국내 의료과학의 발전으로 의료 방사선학은 예전과 다르게 상당히 발전하였다. 의료 방사선영상은 법의 과학의 분야로 사망 원인 분석에 도움이 된다. 그러므로 예비 방사선사로 교육 중인 대구·경북 방사선학과 재학생을 대상으로 법의학 인식 및 관심도 등을 분석하고, 대학에서 관련 교육을 논하려고 한다. 연구는 대구·경북 방사선학과 재학 중인 학생 195명을 대상으로 하였다. 방사선학과 만족도는 3.88 ± 0.820으로 높게 나타났다. 법의학 인식도는 2.30 ± 0.905점으로 낮게 나타났으며, 법의학 관심도는 2.71 ± 0.958점으로 나타났다. 또한, 법의학을 알게 된 동기는 중복응답에 대부분 '영화 및 TV'를 통해 63명(32.3%)으로 나타났으며, '유튜브'가 60명(30.8%)으로 나타났다. 연구 대상자의 전공과 일치하는 법의방사선학 인지도는 중복응답에 법의학 115명(59.0%)보다 낮은 66명(33.8%)으로 낮게 나타났다. 본 연구 결과에서 나타나듯이 대상자들은 방사선학과 만족도는 높으나 전공과 일치하는 법의방사선학 인식도는 낮으며, 법의방사선학의 기초가 되는 법의학 인식도 낮으며 전문성이 낮은 영화 및 TV, 유튜브에서 법의학을 접하게 된다. 곧 전문가 양성에 도움이 되지 않으며, 미래 방사선사의 지향과 거리가 있다. 그러므로 전문적 방사선사 양성을 위해 법의학을 정규과정에 도입이 필요하며, 교과 개편이 어려운 경우 전문가로 구성된 특강이 필요하다. 실질적인 대구·경북 의료계의 요구도 분석이 필요하며, 법의방사선학 교육의 필요성도 분석되어야 한다. 본 연구는 방사선학과 교과목 개편의 기초자료로 활용되어 도움이 되길 바란다. Medical radiography is a field of forensic science and helps analyze the cause of death. Therefore, we will analyze the awareness and interest in forensic medicine among students in the Department of Radiologic technology in Daegu and Gyeongbuk who are being trained as prospective radiographers, and discuss related education at universities. The study targeted 195 students in the Department of Radiological technology in Daegu and Gyeongbuk. The satisfaction level of the Department of Radiological technology was high at 3.88 ± 0.820. The awareness level of forensic medicine was low at 2.30 ± 0.905 points, and the interest level in forensic medicine was 2.71 ± 0.958 points. In addition, the reason for learning about forensic medicine was mostly through 'movie and TV' with 63 people (32.3%), and 'YouTube' with 60 people (30.8%). The awareness of forensic radiology, which matches the research subjects' major, was lower at 66 (33.8%) than the 115 (59.0%) forensic medicine in the multiple responses. As shown in the results of this study, the subjects are highly satisfied with the department of Radiologic technology, but their awareness of forensic radiology, which matches their major, is low. Their awareness of forensic medicine, which is the basis of forensic radiology, is also low, and they come into contact with forensic medicine through movie, TV, and YouTube, which have low expertise. In other words, it is not helpful in training professionals, and it is far from the direction of future radiographers. Therefore, forensic medicine needs to be introduced to the regular curriculum to train professional radiographers, and in cases where curriculum reform is difficult, special lectures composed of experts are necessary. It is necessary to analyze the actual needs of the Daegu and Gyeongbuk medical community, and the necessity of forensic radiology education should also be analyzed. It is hoped that this study will be helpful as basic data for the reform of Radiologic techonology department curriculum.